Detection of K‐ras gene mutation by liquid biopsy in patients with pancreatic cancer. Issue 13 (30th March 2015) - Kinugasa, Hideaki; Nouso, Kazuhiro; Miyahara, Koji; Morimoto, Yuki; Dohi, Chihiro; Tsutsumi, Koichiro; Kato, Hironari; Matsubara, Takehiro; Okada, Hiroyuki; Yamamoto, Kazuhide
<x xml:space="preserve">Abstract</x> BACKGROUND Cell‐free circulating tumor DNA (ctDNA) in serum has been considered to be a useful candidate for noninvasive cancer diagnosis. The current study was designed to estimate the clinical usefulness of genetic analysis for ctDNA by digital polymerase chain reaction in patients with pancreatic cancer. METHODS The authors compared K‐ras mutations detected in endoscopic ultrasound‐guided fine‐needle aspiration biopsy tissue DNA and in ctDNA from 75 patients with pancreatic cancer. K‐ras mutations in the serum of 66 independent, consecutive patients with pancreatic cancer were also analyzed and the authors compared the results with survival rates. RESULTS The frequencies of the mutations in tissue samples at G12V, G12D, and G12R in codon 12 were 28 of 75 samples (37.3%), 22 of 75 samples (29.3%), and 6 of 75 samples (8.0%), respectively. Conversely, the rates of the mutations in ctDNA were 26 of 75 samples (34.6%), 29 of 75 samples (38.6%), and 4 of 75 samples (5.3%), respectively. Overall, the K‐ras mutation rates in tissue and ctDNA were 74.7% and 62.6%, respectively, and the concordance rate between them was 58 of 75 samples (77.3%). Survival did not appear to differ by the presence of K‐ras mutations in tissue DNA, but the survival of patients with K‐ras mutations in ctDNA was significantly shorter than that of patients without mutations in both a development set (P = .006) and an independent validation set (P = .002). The difference was especially evident in cases with a G12V mutation. CONCLUSIONS Analysis of ctDNA is a new useful procedure for detecting mutations in patients with pancreatic cancer. This noninvasive method may have great potential as a new strategy for the diagnosis of pancreatic cancer as well as for predicting survival. Cancer 2015;121:2271–2280. © 2015 American Cancer Society.